2016
DOI: 10.2196/mental.5710
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Adherence to Web-Based Mental Health Interventions: A Systematic Review

Abstract: BackgroundAdherence to effective Web-based interventions for common mental disorders (CMDs) and well-being remains a critical issue, with clear potential to increase effectiveness. Continued identification and examination of “active” technological components within Web-based interventions has been called for. Gamification is the use of game design elements and features in nongame contexts. Health and lifestyle interventions have implemented a variety of game features in their design in an effort to encourage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 68 publications
6
120
1
4
Order By: Relevance
“…Furthermore, using screen media increasingly means using different screen media at the same time (Sigman, 2012b). The elements of games increase interest, motivation, enjoyment and thus engagement (Brown et al, 2016;Cugelman, 2013). Although screen time is associated with childhood obesity and considered to be a risk factor (Arango et al, 2014;Ballard, Gray, Reilly, & Noggle, 2009;Boone, Gordon-Larsen, Adair, & Popkin, 2007;Dietz & Gortmaker, 1985), computer and video games are considered to be less harmful than television (Rey-López, Vicente-Rodríguez, Biosca, & Moreno, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using screen media increasingly means using different screen media at the same time (Sigman, 2012b). The elements of games increase interest, motivation, enjoyment and thus engagement (Brown et al, 2016;Cugelman, 2013). Although screen time is associated with childhood obesity and considered to be a risk factor (Arango et al, 2014;Ballard, Gray, Reilly, & Noggle, 2009;Boone, Gordon-Larsen, Adair, & Popkin, 2007;Dietz & Gortmaker, 1985), computer and video games are considered to be less harmful than television (Rey-López, Vicente-Rodríguez, Biosca, & Moreno, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of health behavior, gamification has shown promising results in encouraging physical activity by turning the ‘work of exercise’ into a game [17]. A recent review published in JMIR Mental Health found no studies had been published explicitly examining the role of gamification features on program adherence with Web-based interventions to manage common mental health disorders [18]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, given the essential role of homework in CBT, they have been conceptualized as a means by which the therapy setting can reach beyond the clinic to the patient’s everyday environment [41]. A mobile homework app may support learning between sessions in numerous ways, including making homework materials accessible and easy to keep track of; aiding memory and understanding of the lesson learned during the treatment session; providing coaching and suggestions (eg, through a help function); promoting intrinsic motivation (eg, through goals and challenges, rewards, feedback on progress [42,43]); facilitating self-monitoring of symptoms and changes (eg, through visual displays); and enhancing homework review and troubleshooting (eg, by summarizing results for discussion). In summary, mobile delivery of homework may provide a means of supporting the continuation of learning during the intervals in between treatment sessions.…”
Section: Introductionmentioning
confidence: 99%